Characterization of olfactory sensory neurons in the red clover seed weevil, Protapion trifolii (Coleoptera: Brentidae) and comparison to the closely related species P. fulvipes. (November 2019) - Carrasco, David; Nyabuga, Franklin N.; Anderbrant, Olle; Svensson, Glenn P.; Birgersson, Göran; Lankinen, Åsa; Larsson, Mattias C.; Andersson, Martin N.
Graphical abstract: Highlights: Olfactory sensory neurons for clover odors were characterized in Protapion trifolii. Olfactory responses are largely conserved in the congener P. fulvipes. Two neuron classes demonstrated clear response shifts between species. The response shifts may underlie different host specificity of Protapion weevils. Abstract: Protapion trifolii and P. fulvipes (Coleoptera: Brentidae) are major pests in European clover seed production. Previous studies have reported a high host plant fidelity of these weevils for red and white clover species, respectively, driven by host plant olfactory cues. Given the specific host preferences observed in these weevils, we aimed to elucidate to which extent such selectivity is reflected in their peripheral olfactory systems. Using an electrophysiological approach, we performed the first functional characterisation of olfactory sensory neurons (OSNs) in P. trifolii to a panel of volatile compounds emitted by red clover plants, and compared the results with the reported OSN types of P. fulvipes . Nineteen OSN classes were characterized in P. trifolii, with the majority of these neurons responding strongly to common volatiles released by the host plant. Based on response profiles, eight of these OSN classes have clear matches to OSN classes in P. fulvipes. The OSN colocalisation patterns and antennal frequency of these classes are similar in the two species . Additionally, the responses of these OSNs are generally highly conserved in the two species, with clear response shifts only revealed for two of the OSN classes. These response shifts in combination with additional response dissimilarities for compounds that vary in abundance between red and white clover plants may underlie the species-specific host preferences. Further behavioural and field experiments should focus on these differentially detected compounds to elucidate their potential role in host selection and use in semiochemical-based control of these pests.